Strategi Sekolah dalam Mencegah Kenakalan Siswa dan Membangun Lingkungan Pendidikan yang Sehat di SMP Muhammadiyah 49 Medan - Muthi'ah, Siti (Yayasan Rahmat Islamiyah, 2024)
This study aims to explore the strategies implemented by SMP Muhammadiyah 49 Medan in preventing student delinquency and creating a healthy educational environment. Student delinquency is a significant challenge for educational institutions, requiring effective management. A qualitative approach was used in this study, employing in-depth interviews and direct observations to gather data from teachers, students, and school staff. The study results reveal that the school employs various strategies, including counseling guidance, strict supervision, and collaboration with students' parents. Additionally, the school provides character development programs and extracurricular activities to foster positive student behavior. These findings highlight the importance of synergy between the school, family, and community in creating an educational environment that supports healthy student development. This strategy is expected to serve as a model for other schools in efforts to prevent student delinquency and build a conducive educational environment.